2018
DOI: 10.1111/and.13023
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and vitamin E supplementation enhances the antioxidant status of spermatozoa and improves semen quality in male dogs with lowered fertility

Abstract: Studies showed a beneficial effect of supplementation with selenium (Se) and vitamin E on semen quality. The aim of the study was to investigate the effect of Se and vitamin E supplementation on the antioxidant status of spermatozoa and semen quality in dogs with lowered fertility. Ten dogs were supplemented daily with Se (6 μg/kg organic Se yeast) and vitamin E (5 mg/kg) per os for 60 days. Control group consisted of 10 males without the supplementation. Semen was collected on day 0, 30, 60 and 90. Sperm qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 49 publications
6
25
0
Order By: Relevance
“…The positive response of Vit. E and Se on sperm motility in our study could be explained due to their antioxidant properties of these nutrients (Domosławska et al, 2018) thereby decreasing oxidative stress during summer (Chauhan et al, 2014). The several previous studies in farm animals showed positive effects of Se and/or Vit.…”
Section: Discussionsupporting
confidence: 62%
“…The positive response of Vit. E and Se on sperm motility in our study could be explained due to their antioxidant properties of these nutrients (Domosławska et al, 2018) thereby decreasing oxidative stress during summer (Chauhan et al, 2014). The several previous studies in farm animals showed positive effects of Se and/or Vit.…”
Section: Discussionsupporting
confidence: 62%
“…Supplementation with antioxidants can lead to sperm improvement, as was demonstrated in a previous report [ 23 ]. In the cases described, supplementation with selenium and Vitamin E as antioxidants also improved the quality of semen and restored fertility in two dogs.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, it seems that CATSPER1 gene expression is more sensitive to Se than CATSPER2. In another study, Se increased semen antioxidant status and sperm parameters in dogs with low sperm quality (Domosławska, Zdunczyk, Franczyk, Kankofer, & Janowski, ). However, as yet there have been no reports regarding the effect of pentoxifylline on CATSPER gene expression.…”
Section: Discussionmentioning
confidence: 89%